Design And Development Of Library Anti-Theft System - Selvamani, Sathish Kumar; Nuurul Syahierah, Othman; M. Z. A., Zulkifle; Keresnan, Khaliswaran (Universiti Malaysia Pahang, 2016)
This project is to design and develop an anti-theft system used in library to detect thefts of library books using a concept of magnetic field where it includes as a feature, the provision of a magnetic element in each book. The system for detecting the theft of such books includes the means for detecting the magnetic elements in such books. The system comprises a metal strip to accompany each book to be detected.[1, 2] This basically use the concept of magnetic sensors detecting the fields associated with magnetic objects.[3] An improvement in systems in which a magnetized metal strip is secured to books and in which magnet-sensing means are provided at an exit from the library to give an alarm if one attempts to remove the books through the exit with the magnetized metal strip. If the metal strip does not undergo demagnetization, its motion will induce currents in the coils to operate an indicator such as alarm or LED.[4-6] [7] In other word, system for detecting the magnetized metal strip consist of detectors sensitive to a magnetic field and with indicators, which may indicate the presence of a strong magnetic field.[8, 9]